الهجرة الداخلية في سورية ودورها في عملية التحضر (Latakia University Journal - Economic and Legal Sciences Series, 2019)
انطلاقا من أهمية دور السكان في عملية التنمية وما يرتبط به من مظاهر ديموغرافية لها دورها في تطوير التنمية، كان من الضروري التطرق لحركية السكان المتمثلة بالهجرة، لما لها من دور بارز في الحياة. وقد أصبحت الهجرة الداخلية في سوريا مشكلة تؤثر بشكل ملموس على واقع الحياة من كافة جوانبها  خاصة وأنها تمت بشكل عشوائي دون تخطيط أو دراسة توجه هذه الظاهرة نحو المسار الصحيح بما يخدم التنمية، لذا جاءت الهجرة في سوريا لتفرز ظواهر سلبية اختلفت من مدينة لأخرى باختلاف العوامل والظروف المؤثرة في حركية السكان، ومن هذه الظواهر سوء التوزع الجغرافي للسكان والتحضر المفرط الذي عانت منه المدن الكبرى. لذا كان من الضروري دراسة وبحث الهجرة الداخلية من جوانبها كافة، وتحليلها ووضع الحلول المناسبة لتلافيها، والحد من آثارها السلبية. Starting from the important role of population in the process of evolution and all the demographic phenomena related to it, it was necessary to tackle the issue of population movement represented by migration for its important role in life. The internal migration in Syria has become a problem that affects all sides of life. This is true because it has been done randomly without any previous study or planning that can direct this phenomenon towards the correct track that serves the developing process. For all of these reasons, the migration in Syria started producing negative phenomenon that differ from one city to another through the different conditions and circumstances affecting the movement of the population. From these phenomena we have the geographic misdistribution of people and the extreme urbanism from which the big cities suffer. So, it was necessary to study the internal migration from all sides, and to analyze it stating the proper solution to avoid it and to restrict its negative effects.